Surface roughness of composite resins after finishing and polishing - Nagem Filho,Halim (2003)
This study evaluated the effect of surface finishing methods on the average surface roughness of resin composites. Seven composites and two polishing systems were used. One hundred and twenty-six conical specimens of each material were prepared in stainless steel molds against a polyester strip. Forty-two of them remained intact and were used as controls. Each half of the remaining samples was polished with either diamond burs or diamond burs + aluminum oxide discs. The results showed no statistical difference in average surface roughness (Ra, µm) between the polyester strip and aluminum oxide discs (p>0.05). However, finishing with diamond burs showed a statistically higher average roughness for all composites (p<0.05). Statistical differences were detected among materials (p<0.05) in the use of diamond burs.